Mapping Global Institutional Typologies: A Hierarchical Clustering Approach to Inclusive–Extractive Governance - Yahya Ayasi; Dedy Yuliawan (CV. ITTC INDONESIA, 2026)
Cross-country income disparities remain a central puzzle in institutional economics, yet most clustering studies are regionally confined or rely on binary classifications that obscure the multidimensional nature of institutional variation. This study constructs a global institutional typology for 100 countries across all major world regions and maps Indonesia's governance profile within it. Hierarchical Clustering Analysis (HCA) was applied to 2023 cross-sectional data using five Worldwide Governance Indicators (WGI) — Voice and Accountability, Political Stability, Government Effectiveness, Regulatory Quality, and Rule of Law alongside the inverted Corruption Perceptions Index (CPI_rev), replacing the redundant Control of Corruption dimension. Countries were selected through purposive sampling ensuring geographic and developmental representativeness, with z-score standardization, Euclidean distance, and Ward.D linkage validated by silhouette width. Two robust clusters emerged: an extractive-tending group (n = 62, mean GDP per capita USD 19,599 PPP) and an inclusive-tending group (n = 38, mean GDP per capita USD 64,720 PPP), a 3.3-fold income gap consistent with Acemoglu and Robinson's (2012) framework. Indonesia's placement in Cluster 1 reveals a paradox: strong democratic and state-capacity indicators coexist with below-average income, with corruption (CPI_rev = 66.00) and weak rule of law as binding constraints. For extractive-tending countries, corruption control emerges as the most urgent reform priority, while inclusive-tending countries should focus on sustaining institutional quality to maintain long-run economic performance. Indonesia's post-reformasi gains require deeper judicial reform and anti-corruption enforcement to translate governance improvements into inclusive economic outcomes.